Utilizing the Kili-Kili Coastal Area as a Living Laboratory: Integrating Hydro-Climatological Stressors into the Geography Curriculum - Yuniar, Yesi; Maharani, Puspa Dewi; Bibot, Sule Haruna; Biantoro , Agung Nugroho (CV Bumi Spasial, 2025)
Understanding the complex interaction between hydro-climatological stressors and agricultural productivity is crucial not only for environmental management but also for fostering geospatial literacy. This study aims to analyze the effects of seawater intrusion and Oldeman climate typology on agricultural productivity in Kili-Kili, Trenggalek, and evaluate these findings as a Contextual Teaching and Learning (CTL) resource. Using a descriptive-explorative design, water quality data (Salinity/TDS) and 10-year rainfall records (2015–2024) were analyzed and mapped against the Indonesian Kurikulum Merdeka learning outcomes. Scientifically, the region is classified as Oldeman Type D2 (3–4 wet months), creating a